Multiple Event Detection In Wireless Sensor Networks Using Compressed Sensing: Health Monitoring Perspective - Rani, Pooja; Gupta, Archna; Singh, Yashwant (International Journal of Computer Sciences and Engineering, 2025)
Wireless Sensor Network (WSN) has tremendous growth due to low cost sensors and well planned techniques. Remote sensor systems are considered as expansive systems made of countless hubs with energy to detect the earth and discuss it with administrator. Event detection in remote systems is a method for handling inspected information specifically on the sensor hubs, accordingly, decreasing the requirement for multi-bounce correspondence with the b ase station of the system. This research has studied the existing work of event detection as well as health monitoring using WSN. We have studied various algorithms for route discovery like trust model and GA (Genetic Algorithm). Also studied about the impacts of health monitoring is done by ANN (Artificial Neural System). The assessment depends on QoS parameters, to be specific, Throughput, Energy Consumption, PDR (Packet Delivery Ratio).